2019
DOI: 10.1002/cbf.3426
|View full text |Cite
|
Sign up to set email alerts
|

IGSF1: A novel oncogene regulates the thyroid cancer progression

Abstract: Thyroid cancer has been continuously increasing and extraordinarily prevalent worldwide. The genetic diagnosis has been widely used in fine needle aspiration. IGSF1, an immunoglobulin superfamily member 1, has been shown to be associated with the regulation of thyroid hormone. But the function of IGSF1 in thyroid cancer has not been explored yet. In this article, we will illuminate the correlation between IGSF1 expression and thyroid cancer. We analysed the level of IGSF1 expression in 55 pairs of tissue sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Some of the genes have also been associated with development of specific tumors, e.g. TAC4 [ 5 ], IGSF1 [ 17 ] and SLC39A8 (ZIP8) [ 24 ]. A prognostic role has also been reported for some of these genes, both negative ( ERRFI1 ) [ 25 ], and positive ( SLC44A3 ) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some of the genes have also been associated with development of specific tumors, e.g. TAC4 [ 5 ], IGSF1 [ 17 ] and SLC39A8 (ZIP8) [ 24 ]. A prognostic role has also been reported for some of these genes, both negative ( ERRFI1 ) [ 25 ], and positive ( SLC44A3 ) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…They proposed that surgical excision of malignant tissue in PCa caused a decrease in oxidative stress and that a higher level of PON3 was associated with lower oxidative stress (Bedİr et al, 2020). Finally, IGSF1 is a novel oncogene regulating the progression of thyroid cancer (Guan et al, 2019); however, no study describing its role in PCa has been reported. The predictive model established here showed good ability to predict DFS or BCR in TCGA, GSE116918, DKFZ2018, MSKCC2010, and ICGC-PRAD-FR datasets.…”
Section: Discussionmentioning
confidence: 99%
“…[330][331][332][333] Typical therapeutic blocking agents employed to target KIT include cabozantinib, dovitinib, masitinib, and pazopanib. [334][335][336] At present, two additional clinical trials (NCT01153750, NCT02115542) wait for final results.…”
Section: Kitmentioning
confidence: 99%